Anti-Inflammatory Medicinal Plants of Bangladesh—A Pharmacological Evaluation - Akhtar, Most. Afia (Frontiers in Pharmacology, 2022)
Inflammatory diseases are considered as major threats to human health worldwide. In Bangladesh, a number of medicinal plants have been used in traditional medicine from time immemorial in the treatment of diverse diseases including inflammatory disorders. This assignment aims at providing the status of the medicinal plants of Bangladesh which are traditionally used in the management of inflammatory disorders and are investigated for their anti-inflammatory prospects using different preclinical studies and, future research directions. The information of medicinal plants assembled in this review were obtained from a literature search of electronic databases like Google Scholar, PubMed and ScienceDirect up to December, 2020 from publications on plants investigated for their anti-inflammatory activities, in which the place of plant sample collection was identified as Bangladesh. Keywords for primary searches were ‘anti-inflammatory’, ‘Bangladeshi’ and ‘medicinal plants’. Criteria followed to include plant species were, plants that showed significant anti-inflammatory activities in I) two or more sets of experiments in a single report, II) same or different sets of experiment in two or more reports and III) plants which are traditionally used in the treatment of inflammation and inflammatory disorders. In this work, forty eight species of medicinal plants have been reviewed which have been used in traditional healing practices to manage inflammatory disorders in Bangladesh. The mechanistic pathways of in vivo and in vitro study models employed for the evaluation of anti-inflammatory properties of plant samples have been discussed. Selected plants were described in further detail for their habitat, anti-inflammatory studies conducted in countries other than Bangladesh and anti-inflammatory active constituents isolated from these plants if any. Medicinal plants of Bangladesh have immense significance for anti-inflammatory activity and have potential to contribute towards the discovery and development of novel therapeutic approaches to combat diseases associated with inflammation. However, the plants reviewed in this article were chiefly undergone through preliminary screening and requires substantial investigations including identification of active molecules, understanding the mechanism of action, evaluation for safety and efficacy to be followed by formulation of safe and effective drug products.